PERSEPSI MASYARAKAT TERHADAP OBJEK WISATA SIWANG NEGERI URIMESSING KECAMATAN NUSANIWE KOTA AMBON - Maisyaroh, Ida; Tjoa, Marthina; Seipalla, Billy (Universitas Pattimura, 2024)
This study was conducted with the aim of determining the perception of the community and visitors towards the tourist area. A quantitative descriptive approach was used in this study. Data collection was carried out through interviews with the community and visitors using a questionnaire. Data analysis was carried out using the Chi square test to see the relationship between respondent characteristics and public and visitor perceptions of tourist attractions. The results of the analysis of the relationship between characteristics and knowledge showed that the Asymp sig value was at age (0.407), gender (0.853), education level (0.407) and occupation (0.294). Relationship of Attitude with age (1,000), gender (0.235), education (0.176) and occupation (0.392). and the relationship of behavior to age (0.428), gender (0.113), education (0.692) and occupation with a value (0.802). For the relationship between visitor characteristics and perception, there was no significant relationship as seen in the Asymp sig value of knowledge to age (0.751), education (0.419) and occupation (0.577). relationship of attitude with age (0.785), gender (0.385), education (0.356) and occupation (0.356). Relationship of behavior with age (0.356), gender (0.828), education level (0.887) and occupation (0.175). While there is a relationship of knowledge with gender (0.040). This can be seen from the higher knowledge of tourist attractions among women compared to men.